The Influence of Liquidity, Solvency and Activity Ratios on Profit Growth of Transportation and Logistics Sector Companies Listed on The IDX for the 2019-2023 - Azzahra Muthmainah; Arif Makhsun; Irawan Irawan (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
This study aims to conduct an empirical test on the effect of financial ratio there are liquidity, solvency, and activity ratios on the profit growth of transportation and logistics sector companies listed on the IDX in 2019-2023. The data collection method uses purposive sampling, namely based on certain criteria so that 21 companies and 105 data are obtained. Data testing uses structural model analysis techniques Sstructural Equation Modeling) with an analysis tool, namely SMART PLS version 3 in data processing. The results of this study indicate that the liquidity, solvency, and activity ratios do not affect the profit growth of transportation and logistics sector companies.